THE CONTRIBUTION OF CONTEXTUAL TEACHING LEARNING (CTL) TO STUDENTS’ READING MOTIVATION - Ananda Faiza Azzahra; Evi Karlina Ambarwati (PROJECT (Professional Journal of English Education), 2021)
This article reports a study aimed to investigate students' motivation in reading comprehension using a contextual learning approach (adapted from Crawford, 2001) and to find out the benefits of Contextual teaching learning in improving reading motivation. This research used a qualitative case research design. The data obtained from several instruments, namely interviews and questionnaires. The findings show that learning using CTL contributed to students' reading motivation. They admitted that the approach allowed them to practice pronunciation, increased their vocabulary knowledge and made Reading activities easier and more enjoyable. Keywords:  Contextual Teaching Learning, Reading Motivation